Serum lactate as a predictor of early outcomes among trauma patients in Uganda - Okello, Michael; Makobore, Patson; Wangoda, Robert; Upoki, Alex; Galukande, Moses (International journal of emergency medicine, 2014)
Trauma is the leading cause of death in the developed world. Accurate assessment of severity of injuries is critical in informing treatment choices. Current models of assessing severity of injury are not without limitations. The objective of this study therefore was to determine the diagnostic accuracy of serum lactate assays in assessing injury severity and prediction of early outcomes among trauma patients. Methods: This was a cross-sectional analytical study. Consecutive series of all eligible patients had a single venous blood sample drawn for lactate assay analysis (index test) and a concurrent Kampala Trauma Score (KTS) II value determination (reference test). Admitted patients were followed up to assess early outcomes (length of hospital stay and mortality). Results: Out of the 502 trauma patients recruited, 108 (22%) were severely injured, 394 (78%) had non-severe injuries, and 183 were admitted. There was a significant difference between median (interquartile range (IQR)) lactate levels among the severely injured (4.3 (2.6, 6.6)) and the non-severely injured (2.4 (1.6, 3.5), p < 0.001). After a 72-h follow-up of the admitted patients, 102 (56%) were discharged, 61 (33%) remained in the hospital, 3 (2%) remained in the ICU, and 17 (3%) had died. The area under the receiver operator characteristic (ROC) curve was 0.75 for injury severity. Serum lactate ≥2.0 mmol/l had a hazard ratio of 1.10 (p < 0.001) for emergency department disposition, 4.33 (p = 0.06) for the 72-h non-discharge disposition, and 1.19 (p < 0.001) for 72-h mortality. Serum lactate ≥2.0 mmol/l at admission was useful in discriminating severe from non-severe injuries with a sensitivity of 88%, specificity of 38%, PPV of 30%, and NPV of 92%.
Keywords: Serum lactate; Injury severity; Trauma; Outcome